Personality Traits and the Growth of Emotional Intelligence. A Systematic Evaluation - Antonopoulou, Hera (Technium Education and Humanities, 2023)
Emotional intelligence (EI) and personality traits are inherent factors that shape individuals’ perception, cognitive processing, and behavioral responses to emotional stimuli. This study examines the complex interplay between personality traits and emotional intelligence (EI), investigating how certain personality traits can impact the formation and expression of EI. By employing a blend of empirical investigation and theoretical examination, we evaluate the correlation between fundamental aspects of an individual’s personality, namely openness, conscientiousness, extraversion, agreeableness, and neuroticism, and their emotional intelligence (EI) capacities, including self-awareness, self-regulation, motivation, empathy, and social skills. This study utilized fourteen articles acquired through a systematic search using the keywords "emotional intelligence and personality" in the Scopus and PubMed databases. An individual’s personality plays a significant role in shaping their emotional intelligence, which in turn has a profound impact on multiple domains of human endeavor. Initial findings indicate that specific personality traits may facilitate developing emotional intelligence (EI), whereas others may pose obstacles that necessitate focused interventions. Acknowledging the interaction between personality and emotional intelligence (EI) presents novel opportunities for comprehensive personal growth, emphasizing the significance of customized approaches encompassing both aspects. This study emphasizes the need for a comprehensive comprehension of human behavior, advocating for approaches that accommodate the distinct interplay between an individual’s personality and emotional intelligence. These strategies aim to enhance personal and interpersonal outcomes to their fullest potential.